Energy Economics Concepts, Issues, Markets and Governance - Bhattacharyya, Subhes C.; SpringerLink (Online service) (London : Springer London, 2011)
Since its modest beginning in the 1970s, the academic and research focus on energy has grown substantially and energy has established itself as an independent, interdisciplinary subject area. It attracts attention from people in a range of different fields including engineers, scientists, geologists, environmentalists, bankers, investors, policy makers and politicians. Energy Economics introduces the basic concepts of energy economics and explains how simple economic tools can be used to analyse contemporary energy issues. Energy Economics is organised into six parts that give the reader a thorough grounding in various key aspects of the subject: basic demand-related concepts and ideas used in energy economics; supply-side economics; energy markets, with specific emphasis on oil, gas and coal; the application of simple economic principles in analysing contemporary energy issues; environmental aspects of energy use; and regulatory and governance issues. Energy Economics is an easily accessible reference book for students of energy economics at the postgraduate level, as well as for a wider interdisciplinary audience. It provides readers with the skills required to understand and analyse complex energy issues from an economic perspective.
1. Introduction to Energy Economics -- 2. Energy Data and Energy Balance -- 3. Understanding and Analysing Energy Demand -- 4. Energy Demand Analysis at a Disaggregated Level -- 5. Energy Demand Forecasting -- 6. Energy Demand Management -- 7. Economic Analysis of Energy Investments -- 8. Economics of Fossil Fuel Supply -- 9. Economics of Non-renewable Resource Supply -- 10. Economics of Electricity Supply -- 11. The Economics of Renewable Energy Supply -- 12. Energy Markets and Principles of Energy Pricing -- 13. Energy Pricing and Taxation -- 14. International Oil Market -- 15. Markets for Natural Gas -- 16. Developments in the Coal Market -- 17. Integrated Analysis of Energy Systems -- 18. Overview of Global Energy Challenges -- 19. Impact of High Energy Prices -- 20. Energy Security Issues -- 21. Investment Issues in the Energy Sector -- 22. Energy Access -- 23. The Economics of Environment Protection -- 24. Pollution Control from Stationary Sources -- 25. Pollution Control from Mobile Sources -- 26. The Economics of Climate Change -- 27. The Clean Development Mechanism -- 28. Regulation of Energy Industries -- 29. Reform of the Energy Industry.
Keywords: Engineering; Engineering economy; Renewable energy sources; Industrial organization (Economic theory).; Business planning; Engineering; Energy Economics; Engineering Economics, Organization, Logistics, Marketing; Industrial Organization; Organization/Planning.; Renewable and Green Energy; Energy Policy, Economics and Management